Perceptual dialectology in northern England: Accent recognition, geographical proximity and cultural prominence. (April 2016) - Leach, Hannah; Watson, Kevin; Gnevsheva, Ksenia
Abstract : Work in perceptual dialectology has argued that listeners' successful identification of accent areas is facilitated by their geographical proximity to a particular region. Montgomery (2007, 2012 ) argues that this proximity effect is mediated by a 'cultural prominence' effect, where localities of high cultural salience seem less distant. We explore these claims using an online survey in which listeners were asked to identify the regional origin of speakers of five accents from England's 'linguistic north' (Liverpool, Manchester, Crewe, Stoke‐on‐Trent and Macclesfield) from audio clips of four different sentences. We show that the proximity and cultural prominence effects are partially supported, and that the proximity effect is driven by listeners' likely contact with/experience of the dialect in question. We also show that listeners react differently to different sentences in the same accent. While some sentences are identified correctly very often, others, even for culturally prominent locations with distinctive accents (i.e. Liverpool), are hardly ever correctly identified. We connect this to the geographical distribution of the linguistic features in the clips, and we argue that the presence, absence and range of individual linguistic features should be systematically considered in all perceptual dialectology work which uses audio stimuli.